2020
DOI: 10.1021/acs.nanolett.0c03584
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution Optical Spectroscopy of Nanoscale Emitters within a Photonic Atom Probe

Abstract: Atom Probe Tomography (APT) is a microscopy technique allowing for the 3D reconstruction of the chemical composition of a nanoscale needle-shaped sample with a precision close to the atomic scale. The photonic atom probe (PAP) is an evolution of APT featuring in situ and operando detection of the photoluminescence signal. The optical signatures of the lightemitting centers can be correlated with the structural and chemical information obtained by the analysis of the evaporated ions. It becomes thus possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…The 3D reconstructed volume of the analyzed system is visualized in Fig. 3 in the section on preliminary TEM characterization and in previous works [16,22]. This phenomenon is reproduced through the depth of the analyzed volume in Fig.…”
Section: D Reconstructionmentioning
confidence: 53%
See 3 more Smart Citations
“…The 3D reconstructed volume of the analyzed system is visualized in Fig. 3 in the section on preliminary TEM characterization and in previous works [16,22]. This phenomenon is reproduced through the depth of the analyzed volume in Fig.…”
Section: D Reconstructionmentioning
confidence: 53%
“…The sawtooth profile is visible when the observation is performed along the polar [0001] direction (c-direction, z axis for the strain/stress tensors) [22]. The [11][12][13][14][15][16][17][18][19][20] adirection corresponds to the y axis for the strain/stress tensors. The orientation of the crystal is also visualized in Fig.…”
Section: Tip Specimen Preliminary Characterization and Crystal Orient...mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of the Zn and O EELS peaks indicated that the grain was composed of ZnO; the Al signal observed in the cluster structure confirmed the presence of the metal atoms inside the grain, suggesting that the sputtered material was, in fact, AZO and not simple ZnO, even at this low deposition thickness. This result was surprising, as the small size of the AZO clusters and the small amount of dopant made their characterization difficult; it is also statistically possible to find undoped nanostructures [ 28 , 29 , 30 , 31 , 32 , 33 ]. Based on findings in the literature, the Al signal at 78 eV in Figure 2 d can be ascribed to the Al-O bond, as expected for the Al-doped ZnO, which presents an atomic structure where the Al 3+ ions substitute Zn 2+ ions in the lattice [ 26 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%